การพัฒนาแผนการเรียนรู้ที่บูรณาการกระบวนการคิดอย่างมีวิจารณญาณกับปรัชญาของเศรษฐกิจพอเพียงสำหรับนักเรียนชั้นมัธยมศึกษาโรงเรียนปรินส์รอยแยลส์วิทยาลัย - วชิระ ครินชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research study aimed to develop the learning plans integrated critical thinking process toward Sufficiency Economy based for Mathayomsuksa 1 students at The Prince Royal’s College in Chiang Mai province. The populations employed in this study were purposive sampling of five experts to evaluate learning plans including one school administrator and four teachers who teach Social Study, Religion and Culture. The instruments in this study were learning plans integrated critical thinking process toward Sufficiency Economy based for Mathayomsuksa 1 students at The Prince Royal’s College, Chiang Mai. For data analysis, means and standard deviation were employed in this study. The data were also presented in tables and examined by Content Analysis. The results of the study reveal that the researcher found out the process of writing learning plans and the elements of learning plans integrated critical thinking process toward Sufficiency Economy based for Mathayomsuksa 1 students at The Prince Royal’s College in Chiang Mai province. In the learning unit plans were comprised of three learning plans entitled 1) “the concepts of Sufficiency Economy Philosophy” 2) “the work and royal development projects initiated by His Majesty the King” and 3) “the utilization of Sufficiency Economy Philosophy” respectively. Meanwhile, it was also found that the overall correspondence evaluation of learning plans was considered to be “very appreciate” ( =2.90) with learning standards/indicators, learning contents, learning objectives, important contents, strands learning activities integrated critical thinking process and the Philosophy of Sufficiency Economy, materials and learning resources, and methods for measuring and evaluating. In conclusion, these three learning plans could be applied to learning management in classes of Social Study, Religion and Culture.